GLOBAL INSIGHTS INTO MODERN INDUSTRIAL POLICIES: ENHANCING MATERIAL RESOURCE EFFICIENCY FOR SUSTAINABLE DEVELOPMENT (Scientific Journal of Actuarial Finance and Accounting, 2024)
Modern industrial policies have evolved significantly, focusing on increasing the efficiency of material resource supply systems to ensure sustainable economic growth. Many countries have developed strategies to optimize material resource management by integrating innovative technologies, enhancing logistics systems, and promoting circular economies. This article examines foreign experiences in the application of industrial policies that improve resource efficiency, focusing on countries such as Germany, Japan, and South Korea. By analyzing their strategies and policies, this study identifies key approaches and provides recommendations for improving the material resource supply systems globally.